Effect of sonication on osmotic dehydration and subsequent air-drying of pomegranate arils. (March 2019) - Allahdad, Zahra; Nasiri, Motahareh; Varidi, Mehdi; Varidi, Mohammad Javad
Abstract: The purpose of this research was to enhance the efficiency of osmotic dehydration through applying ultrasound waves with frequencies of 25 and 40 kHz at different intervals. Subsequently, moisture removal rate was estimated in drying of pre-treated arils. Results showed that ultrasound by inducing more detachment of cell wall increased water loss and solute gain during osmotic dehydration. A 2-fold and 2.7-fold increment for water loss at the frequencies of 25 and 40 kHz, respectively, was observed at the end of process. Microstructural changes also offered a low resistance to water removal in air-drying ahead and effective diffusivity increased by 43% during the first falling rate period and by 66% during the second rate falling rate period for arils predehydrated at the frequency of 40 kHz being more effective than 25 kHz. Magee model because of the lowest values χ 2, RMSE values as well as mean relative deviation modulus adequately described the experimental data of water loss and solid gain during osmotic dehydration and ultrasound-assisted osmotic dehydration. Better color quality was among positive impacts of applying ultrasound along with osmotic dehydration at the expense of losing total anthocyanin content and increasing hardness, as compared to the osmo-dehydrated samples. Highlights: Ultrasonic waves at different time lengths were used during osmo-dehydration of arils. Ultrasound at higher frequencies and more prolonged time enhanced the rate of osmotic dehydration. Magee's model was appropriate for predicting water loss and solid gain values. Higher frequency was helpful in increasing water effective diffusivity during drying.